O-27 Promoting autonomy? Bringing legal analysis to bear on the practical issues associated with ACP implementation. (1st September 2015) - Blake, Meredith; Sinclair, C; Auret, K; Carroll, R; Wilkinson, A
Abstract : Background: Advance care planning (ACP) legislation aims to promote patient autonomy, however there are practical challenges in implementing ACP in healthcare settings. Aim: This study applied legal analysis to an initiative aimed at implementing ACP in one residential aged care facility (RACF). Methods: Case study of a quality improvement initiative, with concurrent legal analysis. The research team and RACF staff (N = 10) collaborated over a year, documenting practical challenges in implementing ACP. Quality improvement methodology was used to develop and trial solutions. Research data included an 'end-of-life wishes conversation tool', staff meeting minutes and resident/family outcomes (satisfaction with conversation tool, number of completed ACP discussions, retrospective audit of end-of-life care). Results: Challenges included staff turnover, high rates of dementia, and difficulties coordinating meetings with family members. Residents, family members and staff rated the 'end of life wishes conversation tool' positively. Where residents lacked capacity due to dementia, a substitute decision-making approach was adopted, with reliance on family members. However staff lacked a robust process for assessing capacity to participate in ACP. Discussion: Implementing ACP in the RACF setting can be problematic. Dementia can erode resident autonomy, and force staff to adopt a substitute decision-making approach, particularly when under time pressure. Quality improvement projects provide rich, contextual data regarding practical challenges, while legal analysis interprets these challenges with reference to intentions underpinning ACP legislation. Conclusion: Further work is required to support decision-making capacity for RACF residents with dementia. This will enable ACP legislation to achieve its aims of promoting patient autonomy.